HUBUNGAN AKSES LAYANAN KESEHATAN SAAT KEHAMILAN TERHADAP KEJADIAN STUNTING - Mareta Kusumawati, Rindha; Apriyani, Apriyani; Wulandari, Kartina; Suwignyo, Suwignyo (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
The incidence of stunting under five is a major nutritional problem faced by Indonesia. Stunted toddlers are toddlers with nutritional status based on length or height for their age with a z-score value less than -2SD and categorized as very short if the z-score value is less than -3SD. Based on data from the Samarinda City Health Office in 2020 the prevalence of stunting is 11.9% and in 2021 it will decrease by 10.7%. North Samarinda District contributed 20% of the total number of cases of stunting. Bengkuring Health Center is the nearest Health Center, which has a distance of approximately 3 km. People in the area choose to self-medicate when a family member is sick. Including when a family member is pregnant, the community rarely visits the Puskesmas to carry out examinations with health workers. The purpose of this study was to look at the relationship between access to health services during pregnancy and the incidence of stunting in North Samarinda sub-district. This study used a quantitative research design with a cross sectional approach and used the chi square test. The research sample is 30 people. The location of the research was in the North Samarinda sub-district and was carried out in July 2022. The results of the study found that there was no relationship between access to health services during pregnancy and the incidence of stunting with a chi-square test of 0.424 < 3.841. Suggestions that Posyandu should regularly monitor stunting incidents.